The Arbitrating Effects of Leadership, Equity, and Integrity on Employee’s Organizational Commitment – A study of Hotels in Jharkhand - Sharma, Viveka Nand; Hans, Arvind (Future Science / FSH-PH Publications, 2022)
Research Aims: Improve organizational commitment through leadership, organizational equity, and Integrity. Design/methodology/approach: A survey method with path analysis techniques to test the direct effect and use Sobel test to test the Arbitrating effect of variable variables: Leadership (X1), Equity (X2), and Integrity (X3), on the Organizational Commitment (Y) at Hotels in India. Data were collected using a questionnaire. The number of samples for the study was 123 respondents drawn from a population of 153 people. Research Findings: Leadership, organizational equity, and Integrity have a positive and significant effect on organizational commitment. That the variable that most affects organizational commitment is the Integrity variable. Whereas for testing the Arbitrating effect, the results obtained are Arbitrating effects of leadership on organizational commitment through Integrity, there is an Arbitrating effect of leadership on organizational commitment through equity, and there is an Arbitrating effect of organizational equity on organizational commitment through Integrity, with the number of Arbitrating effects. It was found that the Arbitrating effects of leadership through equity showed greater results than through Integrity. Theoretical Contribution/Originality: The effect of leadership, equity, and Integrity to increase organizational commitment. Managerial Implication in the South East Asian context: A great organizational commitment from human resources in a hotel, management of hotel could improve the business and adapt in response to situation changes. Research limitation & implications: management of hotels should find a strategic point how to improve organizational commitment of their employees to their company.